Physical causation - Dowe, Phil (Cambridge : Cambridge University Press, 2000)
Physical Causation systematically presents an original and positive perspective on causation: the conserved quantities account of causal processes, which Phil Down has been developing for the past decade. Dowe provides an account of causation grounded in modern science. The book explains causal processes and interactions through the concept of conserved quantities: a causal process is the world line of an object that holds a conserved quantity, and a causal interaction consists of the exchange of these quantities.
1. Horses for courses: causation and the task of philosophy; 2. Hume's legacy: regularity, counterfactual and probabilistic theories of causation; 3. Transference theories of causation; 4. Process theories of causation; 5. The conserved quantity theory; 6. Prevention and omission; 7. Connecting causes and effects; 8. The direction of causation and backwards-in-time causation.
Includes bibliographical references and index.
Keywords: Causality (Physics).